Alternatif Perancangan Jembatan Pelengkung Struktur Atas Jembatan Tawaeli Menggunakan Sistem Jembatan Pelengkung Steel Box Tipe Through Arch Birdge - Palmabas, Suardi; Sariman, Syahrul; Yuniarto, Eka (Program Studi Teknik Sipil Universitas Bosowa, 2025)
The bridge, a structural construction used to cross gaps or obstacles like rivers, railroads, or highways, is essential in infrastructure. Replacing Tawaeli I Bridge is part of the government’s initiative to improve road and bridge infrastructure in Indonesia. Tawaeli I Bridge has nearly reached its planned lifespan and thus requires replacement. The current concrete bridge design includes piers within the river flow, which creates issues, especially during the rainy season when rising water levels and carried debris risk damaging the piers. This study focuses on designing a replacement for Tawaeli I with an upper arch bridge structure using a Steel Box Through Arch Bridge system. The new bridge, spanning 80 meters in length and 10 meters in width, is designed without piers in the river, allowing unobstructed flow. It includes longitudinal IWF 500.200.10.16 girders, transverse IWF 900.500.24.36 girders, D 55 mm freyssinet hangers, an arch Box 1100.1000.50.50, and tension Box 1000.900.50.50. This design uses FEM structural software to analyze the structure and internal forces.